A distributed source locator model for name resolution in named data network - Obaid, Mays Salman (2016)
Recently, the number of devices that are connected to the Internet had been significantly increased with much more expected increment in the future. ICN is a new concept for future Internet that has been developed, many projects within the ICN concept are being researched and NDN in one of them. The purpose of this research is to design distribution source locator for Name Resolution System to avoid the point of failure that may occur if there is only a central system and implemented this new model in NDN architecture to guarantee findings of any object in the network instead of looking for data hop by hop. This research employs the Design Research Methodology (DRM) and introduces its main stages according to the nature of this research. The conceptual model had been designed based on the previous study of NRS in other ICN projects, and according to Chord model in the distributed hash table (DHT). The huge amount of data and unfixed name length in NDN architecture are the main points that must be taken into consideration in order to produce an efficient NRS for NDN. Furthermore, such system simplifies the distributing of the data that correspond to it. NDN is a new project under ICN concept and it is still under research with many issues that is needed to be solved, also there is no real component to work on NDN and all work had been done based on simulation environment. Since the present research focuses on distributing the source locator for NRS, the major contribution of this study is to provide a guaranteed way to find the data object in NDN architecture and to improve the scalability issues in the network. This will support the data routing and transfer between the node and reduce the overall exchanged traffic. This permits the development of solving one of the major open issues in NDN architecture and thus aids in supporting the deployment of the new Internet concept base on the ICN networks. It will thus help users to transfer data reliably and more efficiently. The major contributions of this study include the design of a new Distributed Source Locator (DSL) for Name Resolution. Other contributions are the way of distributing the hash tables for better and faster data lookup, on the other hand, this distribution gives the users the privilege to specify the data levels which results in an increment in the data security of the network. All these would contribute toward the maximized utilization of network resources.